2009
DOI: 10.1177/0961203308099470
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma and systemic lupus erythematosus: a matter of pure coincidence?

Abstract: To describe three cases of meningioma observed in a large cohort of 546 patients with systemic lupus erythematosus (SLE) followed at our Department in the last 15 years. We identified three cases of meningioma among 181 patients with SLE who underwent a brain magnetic resonance imaging (MRI) during their disease course (prevalence 1.65%). All three SLE cases were women with a disease onset at 47-, 18- and 42 -years-old, respectively. All patients presented neuropsychiatric (NP) symptoms and had an incidental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…In the present case, the patient had SLE. The prevalence of meningioma in SLE patients has been reported to be 1.65%, which is higher than the rate of 0.5% in the general population [5]. The relationship between SLE and meningioma has been hypothesized to be rooted in hormonal influences, but this might be a pure coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the patient had SLE. The prevalence of meningioma in SLE patients has been reported to be 1.65%, which is higher than the rate of 0.5% in the general population [5]. The relationship between SLE and meningioma has been hypothesized to be rooted in hormonal influences, but this might be a pure coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…Castellino et al reported three cases of meningioma with lupus erythematosus [8]. The prevalence of meningioma in patients with lupus erythematosus was 1.65% (3 among 181 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and proper treatment of brain involvement in SLE with neuropsychiatric features might decisively influence prognosis. Few occurrences of brain meningioma in patients with SLE have been reported [7,8]. To the best of our knowledge, no SLE patients with brain meningioma have yet been reported from Eastern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Imaginable pathogenic paths linking SLE and cancer include supposed links with medicaments used, patients treated with immunosuppressive or steroid agents, or prolactin and viral contacts, or post-transplantation suggests and toxicity of gamma knife radiosurgery may play a role in the pathogenesis of SLE in some patients. However, risk factors like immunosuppressant, steroid and hormones could be predisposing factors for the development of meningioma during adult life are well known [21].…”
Section: Bymentioning
confidence: 99%